TAUTOS TAPATUMO BEIEŠKANT - Morkūnienė, Jūratė (Problemos, 2008)
Kuzmickas B. Tautos tapatumo savimonë: lietuvių savimonės bruožai.Monografija. Vilnius: MRU, 2007. 207 p.ISBN 978-9955-19-063-9In Search of National IdentityJūratė Morkūnienė span>